The Prostacyclin Analogue, Treprostinil, Used in the Treatment of Pulmonary Arterial Hypertension, is a Potent Antagonist of TREK-1 and TREK-2 Potassium Channels - Cunningham, Kevin P.; Clapp, Lucie H.; Mathie, Alistair; Veale, Emma L. (Frontiers in Pharmacology, 2021)
Pulmonary arterial hypertension (PAH) is an aggressive vascular remodelling disease that carries a high morbidity and mortality rate. Treprostinil (Remodulin) is a stable prostacyclin analogue with potent vasodilatory and anti-proliferative activity, approved by the FDA and WHO as a treatment for PAH. A limitation of this therapy is the severe subcutaneous site pain and other forms of pain experienced by some patients, which can lead to significant non-compliance. TWIK-related potassium channels (TREK-1 and TREK-2) are highly expressed in sensory neurons, where they play a role in regulating sensory neuron excitability. Downregulation, inhibition or mutation of these channels leads to enhanced pain sensitivity. Using whole-cell patch-clamp electrophysiological recordings, we show, for the first time, that treprostinil is a potent antagonist of human TREK-1 and TREK-2 channels but not of TASK-1 channels. An increase in TASK-1 channel current was observed with prolonged incubation, consistent with its therapeutic role in PAH. To investigate treprostinil-induced inhibition of TREK, site-directed mutagenesis of a number of amino acids, identified as important for the action of other regulatory compounds, was carried out. We found that a gain of function mutation of TREK-1 (Y284A) attenuated treprostinil inhibition, while a selective activator of TREK channels, BL-1249, overcame the inhibitory effect of treprostinil. Our data suggests that subcutaneous site pain experienced during treprostinil therapy may result from inhibition of TREK channels near the injection site and that pre-activation of these channels prior to treatment has the potential to alleviate this nociceptive activity.